Nilai Tukar, Market Capitalization, Aktivitas Volume Perdagangan Terhadap Return Dan Abnormal Return Pada Perusahaan Manufaktur - Ivani, Kartika Aprilia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The capital market plays an important role in the life of a country to encourage economic growth. In the capital market, the share price of a company can be used to measure the financial performance of a company, so that under reasonable and normal conditions, the share price of a company can be seen as an increase in its financial performance. A country's stock market is often sensitive to surrounding events, even unusual ones. The aim of the research is to determine the difference in exchange rates on returns before and after the announcement of the first case of the Covid-19 pandemic in automotive and component sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The research approach used is the event study method to analyze the market response to events because it compares differences in exchange rates, market capitalization, trading volume activity on returns and abnormal returns before and after the announcement of the first case of the Covid-19 pandemic in automotive and component subsector companies. listed on the Indonesian Stock Exchange. The research results show that stock trading frequency has no significant effect on stock returns, trading volume has no significant effect on stock returns, market capitalization value has no significant effect on stock returns, stock prices have no significant effect on stock returns, trading days have no significant effect on stock returns.